REFORMASI BIROKRASI KINERJA PEMERINTAHAN DAERAH DALAM MENYELENGGARAKAN OTONOMI DAERAH - Sabrina Sintia; Najua Fauzani; Irhas Khasais; Rizka Maydikta; Mutiara Putri Syahrani; Adinda Salsabila Rizki; Dwi Khusnatun Nisa; Ayu Nur Safitri; Irma Yunita; Ana Mentari; Febra Anjar Kusuma (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Abstrack : Bureaucratic Reform and the Performance of Local Governments in the Implementation of Regional Autonomy: This study examines the urgency of bureaucratic reform to strengthen the performance of local governments in implementing regional autonomy. Regional autonomy provides greater authority for local governments to manage development, public services, and fiscal resources based on local needs, yet its implementation continues to face serious challenges. Using a literature review method, this study analyzes theoretical perspectives, empirical findings, and institutional constraints that affect regional government performance. The findings show that bureaucratic reform is crucial to overcoming structural weaknesses such as hierarchical culture, corruption, low competence, political intervention, and ineffective public services. These challenges significantly hinder the realization of quality public services, equitable development, and fiscal independence. The study highlights that bureaucratic reform must involve strengthening human resources, simplifying structures, improving governance systems, and encouraging innovation to build a transparent, accountable, and performance-oriented local government. The implications of this study emphasize the need for continuous reform to ensure that regional autonomy can function optimally and contribute to sustainable development. Keywords: Bureaucratic Reform; Local Government Performance; Public Services; Regional Autonomy; Governance